PENEGAKAN HUKUM TERHADAP TINDAK PIDANA JUDI ONLINE DI INDONESIA: ANALISIS NORMATIF - Saripudin, Asep; Arafat, Zarisnov; Abas, Muhamad (Universitas Labuhanbatu, 2025)
Ease of access to information contributes to cybercrime, and online gambling is a major activity that negatively affects online gamblers. The advancement of technology also makes it harder for the Indonesian government to track these websites. This study takes a qualitative approach, focusing on legal methods by examining current legal norms, especially those related to online gambling crimes. The study found that law enforcement carries out actions such as arresting and detaining individuals or agents involved in online gambling in Indonesia. To combat online gambling effectively, there needs to be strong cooperation among law enforcement, the government, and the community to reduce its negative effects. This enforcement is clearly outlined in Indonesia's laws and regulations. However, challenges like rapid technological advances and easy access to information and communication complicate the efforts to eliminate online gambling in Indonesia.Keywords: Criminal Law; Law Enforcement; Online Gambling